Extensive Alternative Splicing of KIR Transcripts - Bruijnesteijn, Jesse; van der Wiel, Marit K. H.; de Groot, Nanine; Otting, Nel; de Vos-Rouweler, Annemiek J. M.; Lardy, Neubury M.; de Groot, Natasja G.; Bontrop, Ronald E. (Frontiers in Immunology, 2018)
The killer-cell Ig-like receptors (KIR) form a multigene entity involved in modulating immune responses through interactions with MHC class I molecules. The complexity of the KIR cluster is reflected by, for instance, abundant levels of allelic polymorphism, gene copy number variation, and stochastic expression profiles. The current transcriptome study involving human and macaque families demonstrates that KIR family members are also subjected to differential levels of alternative splicing, and this seems to be gene dependent. Alternative splicing may result in the partial or complete skipping of exons, or the partial inclusion of introns, as documented at the transcription level. This post-transcriptional process can generate multiple isoforms from a single KIR gene, which diversifies the characteristics of the encoded proteins. For example, alternative splicing could modify ligand interactions, cellular localization, signaling properties, and the number of extracellular domains of the receptor. In humans, we observed abundant splicing for KIR2DL4, and to a lesser extent in the lineage III KIR genes. All experimentally documented splice events are substantiated by in silico splicing strength predictions. To a similar extent, alternative splicing is observed in rhesus macaques, a species that shares a close evolutionary relationship with humans. Splicing profiles of Mamu-KIR1D and Mamu-KIR2DL04 displayed a great diversity, whereas Mamu-KIR3DL20 (lineage V) is consistently spliced to generate a homolog of human KIR2DL5 (lineage I). The latter case represents an example of convergent evolution. Although just a single KIR splice event is shared between humans and macaques, the splicing mechanisms are similar, and the predicted consequences are comparable. In conclusion, alternative splicing adds an additional layer of complexity to the KIR gene system in primates, and results in a wide structural and functional variety of KIR receptors and its isoforms, which may play a role in health and disease.